Light-reversible hierarchical patterns by dynamic photo-dimerization induced wrinkles. Issue 34 (14th August 2017) - Hou, Honghao; Li, Fudong; Su, Zhilong; Yin, Jie; Jiang, Xuesong
Abstract : A novel and effective strategy to fabricate light reversible hierarchical patterned surface with self-healing, reversibly tunable adhesion and wettability properties was presented through photo-dimerization induced dynamic wrinkle, also a novel application of the Braille refreshable typography was demonstrated. Abstract : Hierarchical patterns are playing an increasing role for various fields due to their integrated functions. Herein we created a novel library of multi-scale complex patterns where hierarchical wrinkles can be dynamically generated and eliminated by in situ photo-control. Atom Force Microscopy (AFM) results and UV-vis kinetics manifest that the change of surface modulus induced by dynamic photo-dimerization of the anthracene-containing polymer (PAN) top-layer plays a crucial role in triggering the morphology switch of the resulting wrinkled surface with self-healing, tunable adhesion and wettability properties. Based on the temporal and spatial characteristics of dynamic photo-dimerization, the ordered and hierarchical patterns can be obtained through adapting selective exposure and photolithography. Furthermore, a series of hierarchical patterns in which the smaller-scale wrinkles can be prescriptively generated on the assigned micro-pillar arrays, making up sets of Braille characters, was demonstrated for Braille text refreshable typography through photo-reversible formation and erasure. This novel and effective approach for photoreversible hierarchical wrinkle patterns offers great promise for smart devices and surfaces with dynamic tunable morphology and surface properties on demand in response to light stimuli without altering the bulk properties.